A salvaguarda da criatividade em Paul Ricoeur face ao estruturalismo de Lévi-Strauss - Castro, Maria Gabriela (2019)
In the sixties, between 1960 and 1969, the emergence of Freud’s psychoanalysis and Claude Lévi-Strauss’ structural anthropology takes place. These two approaches question the dimensions of truth, of meaning and of creativity in the thought of French philosopher Paul Ricoeur and force him to a new stage in his philosophical course. In the universe of the conflict of interpretations, Ricoeur would have to face the new challenges that were put to the hermeneutical model of approaching symbolism, mainly in the language and anthropology areas. This study aims at enhancing the key points of the analysis-critique of hermeneutics in Paul Ricoeur in face of structuralism so that it can bring forth the hiatus of creativity in the “science of signs” versus “the philosophy of the meaning of symbols”. How Paul Ricoeur regards the new paradigm of philosophical intelligibility means that he congregates under the same designation of structuralism linguistics, as it originates in Ferdinand de Saussure, Roland Barthes’ semiology, A. J. Greimas’ semiotics and literary critique as represented by G. Genette, inasmuch all these authors have in common the fact that they “confine themselves to the structures of the text, without any reference to the author’s possible intention”. It is here that Ricoeur includes Lévi-Strauss and the science of myths published under the title Mythologiques (4 volumes); and it is precisely through the analysis-critique of this work that Ricoeur keeps a vigorous debate going with Lévi-Strauss in “Réponses à quelquer questions”, the text chosen as the main idea underlying this our approach to structuralism, having as problematizing issue creativity. This option arises from the fact that in this philosophical confrontation structuralism enhances the marginalization of the theme imagination. Nevertheless, and because we detected two nuclear points that interconnect with it — the postponement of history and of creativity in relation to the priority of structure — we ask: will Paul Ricouer adopt a position capable of safeguarding the dynamics of creativity?